PERIBRONCHIAL ADMINISTRATION OF ANTIBIOTICS IN THE INTEGRAL TREATMENT OF PNEUMONIA IN CASE OF ACUTE POISONING - T. P. Pinchuk; A. V. Kurenkov; K. K. Ilyashenko; T. V. Klokova; E. D. Menshikova (Туберкулез и болезни лёгких)
Goal of the study: to improve treatment results of nosocomial pneumonia being the complication of severe acute exogenous poisoning through endoscopic peribronchial administration of anti-bacterial agents.Materials and methods. The analysis included data and treatment results in two groups of patients (71 patients) staying in the emergency care department and suffering from hospital pneumonia as a complication of severe acute exogenous poisoning. Treatment of patients in the compared groups was performed as per the same regimen, anti-bacterial medications were prescribed with the consideration of the drug susceptibility of the causative agents. The difference was the use of the endoscopic peribronchial administration of antibiotics in the main group (41 patients), this technique was not used in the comparison group.Results. Endoscopic peribronchial administration of amikacin to which the isolated causative agent was susceptible, allowed reducing the mortality down to 12/41, 29.0% compared to the group where this method was not used – 13/30, 43.3% (p < 0,05).